My, my moringa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
You may know it as the horseradish tree, drumstick tree, ben tree, benzolive tree or Nebeda: the Moringaceae group of 14 species of which Moringa oleifera is the best-known. Modern enthusiasts rediscovering Moringa call it the Miracle tree ...